If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -8x = 6x + 4 Combine like terms: 10x + -8x = 2x 2x = 6x + 4 Reorder the terms: 2x = 4 + 6x Solving 2x = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 2x + -6x = 4 + 6x + -6x Combine like terms: 2x + -6x = -4x -4x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 -4x = 4 + 0 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| 9(2n-2)=(3n+6)+5 | | 1/3x+18=0 | | 304-17=7x | | 3.6x-0.6y=-1.1y | | v^7=8 | | 2x-32=11x-58 | | 9y^2-25x^4=0 | | 3b+(-4)=-16 | | 2x-32=11x+58 | | 6-3x=2-2x | | 1*1+6+9-5-9=0 | | 3y-9=-30 | | x/2+9=28 | | 7/x=8/12 | | 9-x^4=0 | | 8r^2+3r+2=7 | | n-3/4=-11/4 | | 29/12=-13/4+k | | -2(t-1)+5t=7t-9 | | (p+4)(p+4)=7(p+4)-12 | | 7x=1132 | | 37/7+k=167 | | 8(y-4)/5=-2y | | 4n=-5+4.5 | | 6.5=0.5n+2.5 | | x-5/4=-6 | | 2(7x+4)+6=14x+14 | | -3b-5=-26 | | 28/3=5/3n | | 14=6+z/2 | | 7x+6=7(x-1) | | x-1/2=5/4 |